DEVELOPMENT OF A DEVICE FOR MEASURING AND ANALYZING VIBRATIONS - Stakhova, Anzhelika; Kvasnikov, Volodymyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
It is known that vibration is generated to one degree or another by all moving parts of machines. Vibration processes arising in the process of functioning of machines and equipment are highly informative, reflecting the technical condition of many parts and assemblies quite fully. Therefore, the use of vibration diagnostics systems makes it possible to determine a defect even at the stage of inception, thereby excluding emergency stops of machinery. An urgent task is to create a vibration analysis device, which consists of a sensor for measuring vibration, the principle of operation of which is based on the use of a direct piezoelectric effect. The output signal of the sensor will go to a personal computer or any other device with the Windows operating system, where a spectral analysis of the measured vibration signal is carried out using a Matlab-based diagnostic program.